IMPLEMENTASI MODEL PEMBELAJARAN MURDER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP/MTS - Hafifah Hadiztia; Sari Herlina (Universitas Muhammadiyah Semarang, 2023)
The study aims to see the average mathematics learning outcomes of Class VIII SMP/MTs students through the implementation of the MURDER learning model. The form of research is a quasi-experimental with a research design of nonequivalent control group design. Data collection techniques used in the study were test techniques (pretest and posttest) and observation sheets. From the data on the results of observing teacher activity, the percentage of teacher activity obtained was 87.5% and at the 2nd and 3rd meetings, the percentage obtained was 94.3% and 100% respectively and this was included in the very good criteria and based on inferential data analysis, posttest data obtained . This means that the average mathematics learning outcomes of experimental class students using the MURDER learning model are better than the control class using the conventional learning model.